Challenges of agricultural law in the current context of climate change and the energy and digital transformation in Spain - Sanchez Hernandez, Angel (Przegląd Prawa Rolnego, 2024)
The agri-food sector carries great economic and social importance. It is a key sector for meeting demographic challenges, combating rural depopulation and achieving territorial balance, as well as for the balance of trade itself. Strengthening the agri-food sector is necessary in order to overcome crisis situations, and to improve not only the guarantee of food supply and food security, but also the climate and environmental objectives and the decarbonisation of the economy.